Does R&D factor create a better assets pricing model? Evidence from FTSE 350 - ZHOU, YI (2010)
In this paper, the effectiveness of the Fama and French three factor model and the Al-Horani R&D model are compared under two different portfolio sets for two different testing periods. The two portfolio sets are 9 size & book to market portfolios and 15 industry portfolios respectively. The two testing periods are July 1996-June 2008( 144 months) and July 2002-June 2008 (72 months) respectively. Both time series regressions and Cross sectional regressions are conducted to test whether one model always works better than the other model. A few previous literatures confirmed that adding additional R&D factor to the Fama and French model will improve the explanatory power and the R&D model is better than the Fama and French three factor model. However, the result in this paper show there are portfolio specific and period specific characteristics in these two models, therefore, it cannot be concluded that the R&D model always works better than the Fama and French three factor model.